2011
DOI: 10.1002/joc.2096
|View full text |Cite
|
Sign up to set email alerts
|

The hydro‐meteorological estimation of probable maximum precipitation under varying scenarios in Sri Lanka

Abstract: Probable maximum precipitation (PMP) is widely used as an input in rainfall-runoff modelling to estimate probable maximum flood (PMF), which is required for the design of spillways of large dams. In relation to dam safety studies at 32 dam sites, an analysis was done of extreme rainfalls in Sri Lanka, which is influenced by the Asian monsoon system and cyclonic effects. Accordingly, the Hershfield's statistical method, which is one of the recommended procedures of the World Meteorological Organization (WMO), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Probable maximum precipitation (PMP) is defined as “ the greatest depth of precipitation for a given duration meteorologically possible for a design watershed or a given storm area at a particular location at a particular time of year ” [ World Meteorological Organization , ], and it represents the largest rainfall that could physically occur under a series of adverse atmospheric conditions [ Casas et al ., , ; Douglas and Barros , ; Schreiner and Riedel , ; Fernando and Wickramasuriya , ]. Distinguished from the statistically based T ‐year extreme rainfall estimate that associates depth with annual exceedance probability (AEP = 1/ T ) [see Kao and Ganguly , ], PMP is the deterministic upper bound of extreme storms.…”
Section: Introductionmentioning
confidence: 99%
“…Probable maximum precipitation (PMP) is defined as “ the greatest depth of precipitation for a given duration meteorologically possible for a design watershed or a given storm area at a particular location at a particular time of year ” [ World Meteorological Organization , ], and it represents the largest rainfall that could physically occur under a series of adverse atmospheric conditions [ Casas et al ., , ; Douglas and Barros , ; Schreiner and Riedel , ; Fernando and Wickramasuriya , ]. Distinguished from the statistically based T ‐year extreme rainfall estimate that associates depth with annual exceedance probability (AEP = 1/ T ) [see Kao and Ganguly , ], PMP is the deterministic upper bound of extreme storms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this factor is not taken into consideration, which reduces the methodology to equation (4), where the maximization is determined only by the moisture factor, as explained in Section 2.5.2. As a consequence of this assumption, lower PMP estimations are obtained, as Fernando and Wickramasuriya (2010) concluded.…”
Section: Traditional Hydro-meteorological Methodsmentioning
confidence: 63%
“…Table 2 indicates that the HM2 method gives PMP values 35% smaller than the HM1 method for the BL period; this could change if we also included the amplification by a wind factor in order to evaluate more possibilities, as proposed by Fernando and Wickramasuriya (2010). These authors conclude that the double-maximized HM2 method is similar to Hershfield's PMP estimation.…”
Section: Discussionmentioning
confidence: 91%
“…The conventional moisture maximization method involves only the moisture factor (e.g., moisture content or precipitable water) (Chavan and Srinivas, ). Wind, as a typical dynamic factor with easy access, is combined with the moisture maximization method to develop the MWM approach (Fernando and Wickramasuriya, ; Boota et al ., ). The MWM approach involves maximizing wind and moisture conditions that affect the occurrence of rainstorms, the moisture and wind maximization factor (MWMF) is expressed by Equation , but before use, surface dew point data corresponding to observed storms should be collected for precipitable water calculation (Fernando and Wickramasuriya, ; Boota et al ., ). MWMF=VmWmVdWd where W d is the precipitable water corresponding to the 12‐hr persistent dew point, mm; W m is the maximum precipitable water corresponding to the highest dew point within the study duration, mm; V d is the average 12‐hr persistent wind speed for the observed storm, m/s; and V m is the maximum average observed wind speed within the study duration, m/s.…”
Section: Methodsmentioning
confidence: 99%